Human Skin-Derived Mast Cells Spontaneously Secrete Several Angiogenesis-Related Factors - McHale, Cody; Mohammed, Zahraa; Gomez, Gregorio (Frontiers in Immunology, 2019)
Mast cells are classically recognized as cells that cause IgE-mediated allergic reactions. However, their ability to store and secrete vascular endothelial growth factor (VEGF) suggests a role in vascular development and tumorigenesis. The current study sought to determine if other angiogenesis-related factors, in addition to VEGF, were also secreted by human tissue-derived mast cells. Using proteome array analysis and ELISA, we found that human skin-derived mast cells spontaneously secrete CXCL16, DPPIV, Endothelin-1, GM-CSF, IL-8, MCP-1, Pentraxin 3, Serpin E1, Serpin F1, TIMP-1, Thrombospondin-1, and uPA. We identified three groups based on their dependency for stem cell factor (SCF), which is required for mast cell survival: Endothelin-1, GM-CSF, IL-8, MCP-1, and VEGF (dependent); Pentraxin 3, Serpin E1, Serpin F1, TIMP-1, and Thrombospondin-1 (partly dependent); and CXCL16, DPPIV, and uPA (independent). Crosslinking of FcεRI with multivalent antigen enhanced the secretion of GM-CSF, Serpin E1, IL-8, and VEGF, and induced Amphiregulin and MMP-8 expression. Interestingly, FcεRI signals inhibited the spontaneous secretion of CXCL16, Endothelin-1, Serpin F1, Thrombospondin-1, MCP-1 and Pentraxin-3. Furthermore, IL-6, which we previously showed could induce VEGF, significantly enhanced MCP-1 secretion. Overall, this study identified several angiogenesis-related proteins that, in addition to VEGF, are spontaneously secreted at high concentrations from human skin mast cells. These findings provide further evidence supporting an intrinsic role for mast cells in blood vessel formation.